استخدام الطريقة Mind Mapping لترقية تعلم المفردات لدى الطلاب - Teuku Sanwil; Zaza Maulina (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2022)
This research aims to know the process of teaching and learning vocabulary using the Mind Mapping method, and to know the effectiveness of the process of teaching and learning vocabulary using the Mind Mapping method. The research method that the researcher used was the procedural research method. In order to collect the data, the researcher observed and presented the pre- and post-test for the two roles. As for the results of the research, it was the use of the mind-mapping method in learning vocabulary effective based on the average result when the students obtained the criteria for the results of the completion limit (KKM) in terms of the average result obtained from the second round 81, 42 and the percentage of 90.47% for the degree of success.